A new diphenyl ether from Parmotrema indicum Hale growing in Vietnam. Issue 19 (21st September 2022) - Do, Thanh-Hung; Nguyen, Thanh-Trung; Dao, Thi-Bich-Ngoc; Vo, Huu-Canh; Huynh, Bui-Linh-Chi; Nguyen, Thi-Anh-Tuyet; Mai, Dinh-Tri; Vo, Thi-Phi-Giao; Sichaem, Jirapast; Nguyen, Ngoc-Hong; Duong, Thuc-Huy
Abstract: Chemical investigation of the lichen Parmotrema indicum Hale led to the isolation of one new diphenyl ether, parmetherine D (1 ), along with eight known compounds (2-9 ). The structures were determined by analysis of MS and NMR data and by comparison with the literature. Compounds 1, 2, and 7 were evaluated for α -glucosidase inhibition. Only compound 1 exhibited significant inhibition.